Job Boredom and Counterproductive Work Behavior: The Moderating Role of Self-Control (A Study on Civil Servants of the Provincial Government of “X”) - Thenisia Warinta; P. Tommy Y. S. Suyasa; Raja Oloan Tumanggor (Eduvest - Journal of Universal Studies, 2026)
State Civil Apparatus (ASN) remains one of the most sought-after professions in Indonesia. In carrying out their duties, ASN are bound by laws and regulations, particularly those regarding ASN discipline. Data from the State Civil Service Agency indicate that ASN disciplinary violations throughout 2024 reached 4,195 cases. This study investigates the relationship between job boredom and counterproductive work behavior (CWB) among civil servants in Indonesia, while examining the moderating role of self-control. Amid high rates of disciplinary violations among State Civil Apparatus (ASN), there is a pressing need to understand the psychological drivers of these detrimental workplace behaviors. The research aims to determine whether job boredom predicts CWB and whether an individual’s self-control can mitigate this relationship. Using a quantitative correlational approach, the study collected data from 185 civil servants (109 males and 76 females, aged 24–58 years) in the Provincial Government of "X" via questionnaires measuring job boredom, self-control, and interpersonal and organizational CWB. The results showed that job boredom has a positive and significant influence on counterproductive work behavior, both interpersonally (PKK-I) and organizationally (PKK-O). Self-control was also found to significantly moderate the relationship between job boredom and counterproductive work behavior. The results of this study are expected to provide better insight into alternative recruitment and training strategies for employees, especially civil servants in Indonesia.